Hubungan Penggunaan Tas Punggung dengan Kejadian Nyeri Muskuloskeletal pada Pelajar SMA - Solo, Godilia; Wahyuni, Octavia D. (Universitas Sam Ratulangi, 2025)
Abstract: Backpack is still quite popular among high school students, albeit, inappropriate usage of backpacks can cause side effects in the form of pain complaints in the musculoskeletal system. This study aimed to determine the relationship between backpack usage and musculoskeletal disorders among high school students. This was an observational and analytical study with a cross-sectional design. Samples were high school students grades X-XI of SMA Regina Pacis Jakarta obtained by using concecutive non-random sampling method. Data of musculoskeletal pain using the Nordic body map (NBM) questionnaire were accompanied by measurements of backpack weight, body weight, and height. The results otained 94 students as samples. Students who used backpacks appropriately and did not experience musculoskeletal disorders were 12 people (92.3%), while students who used backpacks inappropriately and experienced musculoskeletal disorders were 20 people (24.7%). Analysis of the relationship between variables using the Fisher’s Exact test obtained a p-value of 0.285, and a PR-value of 3.21. In conclusion, there is no significant relationship between backpack usage and musculoskeletal disorder among high school students of SMA Regina Pacis Jakarta. However, students who use backpacks inappropriately can experience musculoskeletal disorders 3.21 times greater than students who use backpacks appropriately. Keywords: backpack usage; musculoskeletal disorder; students Abstrak: Penggunaan tas punggung di kalangan siswa sekolah menengah atas (SMA) masih cukup diminati, namun penggunaan tas punggung yang tidak sesuai dapat menimbulkan efek samping berupa keluhan nyeri pada sistem muskuloskeletal. Penelitian ini bertujuan untuk mengetahui hubungan antara penggunaan tas punggung dengan gangguan muskuloskeletal pada pelajar SMA. Metode penelitian ialah analitik-observasional dengan desain potong lintang. Sampel penelitian yaitu pelajar SMA Regina Pacis Jakarta kelas X- XI berjumlah 94 orang. Pengambilan sampel menggunakan metode concecutive non random sampling. Pengambilan data nyeri muskuloskeletal menggunakan kuesioner Nordic body map (NBM), disertai pengukuran berat tas punggung, berat badan, dan tinggi badan. Hasil penelitian mendapatkan pelajar yang menggunakan tas punggung dengan tepat dan tidak mengalami gangguan muskuloskeletal sebanyak 12 orang (92,3%) sedangkan pelajar yang menggunakan tas punggung tidak tepat dan mengalami gangguan muskuloskeletal sebesar 20 orang (24,7%). Uji analisis hubungan antar variabel menggunakan uji Fisher’s Exact Test mendapatkan p=0,285 dan nilai PR=3,21. Simpulan penelitian ini ialah tidak didapatkan hubungan bermakna antara penggunaan tas punggung dengan gangguan muskuloskeletal pada pelajar SMA Regina Pacis Jakarta, namun, pelajar yang menggunakan tas punggung tidak tepat dapat mengalami gangguan muskuloskeletal 3,21 kali lebih besar dibandingkan pelajar yang menggunakan tas punggung dengan tepat. Kata kunci: penggunaan tas punggung; gangguan muskuloskeletal; pelajar